2022
DOI: 10.1097/cad.0000000000001472
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of gemcitabine, cisplatin, and bevacizumab for first recurrent and refractory ovarian clear cell carcinoma Kansai Clinical Oncology Group-G1601

Abstract: Patients with advanced ovarian clear cell carcinoma (CCC) have a poor prognosis in the absence of an effective standard treatment. Combination therapy with gemcitabine, cisplatin, and bevacizumab (GPBev) is promising for ovarian CCC. Thus, we conducted a multi-institutional, phase II trial in Japan to examine the efficacy and safety of GPBev for CCC. This is the first study on the use of GPBev for CCC. Eighteen patients (median age, 56.5 years) with pathologically confirmed first recurrent or refractory CCC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Treatment strategies for CCC typically depend on the identified primary site and may involve a combination of surgical resection, chemotherapy, and targeted therapies. In ovarian clear cell carcinoma, platinum-based chemotherapy is the mainstay of treatment, but targeted therapies such as bevacizumab (a monoclonal antibody targeting vascular endothelial growth factor) are being investigated in clinical trials [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment strategies for CCC typically depend on the identified primary site and may involve a combination of surgical resection, chemotherapy, and targeted therapies. In ovarian clear cell carcinoma, platinum-based chemotherapy is the mainstay of treatment, but targeted therapies such as bevacizumab (a monoclonal antibody targeting vascular endothelial growth factor) are being investigated in clinical trials [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis of a multicenter, Phase 3, randomized, controlled trial (JGOG3017/GCIG) comparing TC (carboplatin and paclitaxel) and CPT-P (irinotecan and cisplatin) therapy in patients with recurrent or persistent OCCA found that patients with platinum-resistant relapse had a signi cantly shorter median post-progression survival (PPS) compared to those with platinum-sensitive relapse [8]. Combination therapy with gemcitabine, cisplatin, and bevacizumab (GP + Bev) has also been reported to be promising for advanced OCCA [9]. The identi cation of molecules involved in paclitaxel resistance in OCCA may provide an opportunity to improve the e cacy of paclitaxel and carboplatin regimens in OCCA.…”
Section: Introductionmentioning
confidence: 99%